Laboratory static compression test of aluminium - Kannnan Ponnambalam (Nanyang Technological University, 2020)
The title of the Final Year Project (FYP) report is Laboratory static compression test of aluminium, P-B017. The aim of the project is to perform compressive testing on aluminium specimens under specified settings. The test methods will adhere to the American Society for Testing Materials (ASTM) Standards. The ASTM standard for this project is based on Compression Testing of Metallic Material at Room Temperature (ASTM E9-09). The objective of this report is to evaluate the behaviour of Aluminium Specimens (AL606-T6) under compressive stress following ASTM E9-09 standards. Evaluate the compressive strength, yield strength and elastic modulus of the specimen. The scope of this project is to use a long length specimen according to ASTM E9-09 standards using Shimadzu AG-X Plus 100KN testing machine. The report is divided in 5 sections beginning with the introduction which describes the background, rationale and the objectives of this project. The second section is the literature review of this project and it explains about the ASTM E9-09 test methods, terminologies, material description. The third section explains the preparation needed for the specimen. The fourth section explains experiment set-up and procedures, the fifth section covers the experiment results and discussion and the final section concludes the experiment based on the ASTM E9-09 test methods and recommendations and ideas on how to improve the testing method.